AB1266 Performance of a patient-based online-questionnaire to identify patients with axial spondyloarthritis (SPA) in patients with chronic low back pain. (23rd January 2014) - Brandt, H.; Vahldiek, J.; Rudwaleit, M.; Sieper, J.
Abstract : Background: Between first symptoms and making a diagnosis of axial spondyloarthritis (SpA) there is still a delay of 5-7 years. Effective treatments for active disease have become available. Several strategies for making an earlier diagnosis have been proposed (1), focusing on primary care physicians and orthopaedists and having proven effectiveness in daily clinical practice (2, 3). Objectives: To evaluate the performance of a patient-based online-questionnaire in identifying patients with axial SpA. Methods: Patients suffering from chronic low back pain without diagnosis were asked to complete an online-questionnaire offered on the homepage of our rheumatologic clinic asking, among other parameters, for onset and duration of back pain, type of back pain, presence of other SpA-typical manifestations, elevated ESR or CRP, HLA-B27-positivity, and results of imaging (if available). Following a recent published diagnostic algorithm, the likelihood ratios of these features and the post test probability (PTP) were automatically calculated (1). Patients achieving a PTP of ≥50 received an identification number and were recommended to present to our clinic for further work-up. Results: To date 97 cases were collected and diagnosed. Of these, 14 were diagnosed as axial SpA (n=14/97: 14.4%); 7 fulfilling the modified New York Criteria and 7 being diagnosed as early axial SpA. In 79 of 97 patients an axial SpA was excluded and 4 of 89 patients were diagnosed as possible axial SpA. Of the diagnosed axial SpA patients, 10 of 14 (71.4%) had reached a calculated PTP of ≥90; but also 3 out of 4 (75%) with possible axial SpA and 36 of 79 (45.6%) patients with a diagnosis of non-SpA presented with a PTO of ≥90. If only focussing on those patients presenting with a PTP of ≥90 (n=49), a diagnosis of axial SpA was made in 20, 4% (n=10/49) Thus, the rheumatologist would have to see 5 referred patients to identify one axial SpA patient. The sensitivity of such an approach would be 71.4% (10 out of 14). In the patients with a PTP of ≥90 and excluded diagnosis of axial SpA (n=36) other inflammatory diagnoses like psoriatic arthropathy/arthritis (n=7) or peripheral SpA (n=2) were made, partly explaining the high PTP. Conclusions: A patient-based online-questionnaire to identify patients with axial spondyloarthritis (SpA) in patients with chronic low back pain seems to be of limited value resulting in relatively low percentage of diagnosed axial SpA patients, in comparison to referral programmes in collaboration with primary care physicians (2, 3). References: Rudwaleit M. et al. Ann Rheum Dis. 2004 May;63(5):535-43. Brandt H et al. Ann Rheum Dis. 2007 Nov;66(11):1479-84. Poddubnyy D, et al. J Rheumatol. 2011 Nov;38(11):2452-60. Disclosure of Interest: None Declared